Catherine Smith: capstone - Smith, Catherine, artist (Colorado State University. Libraries, 2023)
The artist's statement: My name is Cat Smith. I focus my work mainly on graphic design, but I also do printmaking and drawing. Because of my multiple interests, I tend to lean towards the more illustrative side of design. I often begin every project with sketches on paper. I feel that I can generate ideas quicker and get more creative results doing it that way. Once I'm out of the ideation stage, I usually gravitate towards a fully digital approach to my work. My process includes a lot of experimentation. I tend to have projects that look very different from my initial sketches. My ideas may be fully formed when I'm beginning a project, but they almost always change. The final product is always influenced by experimenting throughout the creative process. My design work is usually inspired by learning. With each project, I try to use a new technique or learn how to use a new tool that I haven't done before. I feel that expanding my abilities while still in school will better prepare me for whatever design job I end up getting in the future. Because of my experimentation, I have a broad range of work. I have some pieces made fully on my laptop, some that are all hand drawn with my iPad, and some that incorporate both digital and analogue work. I believe this exploration has made me more well-rounded as a designer, and as a creative.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design